Bovine leukemia virus - Burny, Arsene; Willems, Lucas (Henry Stewart Talks, 2007)
Viral replication of bovine leukemia virus, Transmission and pathogenesis in natural and experimental hosts, Dynamics of cell accumulation, Novel therapeutic approach
Reviewed at 2017/05/31